CONNECTING TRANSLATION EMPLOYERS AND TRAINERS. EXPERIENCE OF INTERNSHIPS IN PUBLIC SERVICE INTERPRETING AND TRANSLATION TRAINING - Valero-Garcés, Carmen (Vertimo studijos, 2017)
The University of Alcalá, Madrid, offers a 1-year Master’s Degree course in Public Service Interpreting and Translation (PSIT). The curriculum is based on the principle of cross-fertilization of the three main parameters of training, research and practice. The implementation of this principle in practice means alliances and cooperation with all stakeholders that in one way or other participate in the translation and interpreting (T&I) working environment. Special attention needs to be paid to the job market and to the real recruitment conditions, as well as to the requirements for professional translators and interpreters. In the present article the focus is on one of the main parameters of a successful curriculum, i.e. practice in training, or internships. Internships serve as an introduction to the workplace. The pros and cons of the experience are discussed from three points of view: that of trainers, institutions and students. The informatikon obtained from all three parties has revealed both strong and weak points of the process, but it helped to know what happened outside and inside the classroom for both sides—PSIT students and trainers, on the one hand, and providers of public services on the other. Conclusions serve as feedback and are taken into account when trying to improve educational aspects.